Antioxidant and Anti-Inflammatory Effects of Carotenoids in Mood Disorders: An Overview - Paweł Rasmus; Elżbieta Kozłowska (MDPI AG, 2023)
Depression has a multifactorial etiology comprising family history and unemployment. This review aims to summarize the evidence available for the antioxidant and anti-inflammatory effects of carotenoids in mood disorders. This review article's methodologies were based on a search of the PubMed database for all linked published papers. Epidemiological studies indicate that a diet rich in vegetables, fruits, nuts, fish, and olive oil may prevent the development of depression. Antioxidant supplementation has been found to combat various stress-induced psychiatric disorders, including depression and anxiety. A growing body of evidence indicates that carotenoids have both antioxidant and anti-inflammatory. Studies also suggest that poor dietary intake, particularly low intakes of fruit and vegetables and high intakes of fast food and other convenience foods, may increase the risk of developing depression. Thus, dietary interventions have the potential to help mitigate the risk of mental health decline in both the general population and those with mood disorders. Considering that carotenoids have both antioxidant and anti-inflammatory effects, it is expected that they might exert a promising antidepressant effect. Nevertheless, further studies (including interventional and mechanistic studies) assessing the effect of carotenoids on preventing and alleviating depression symptoms are needed.